FUNGSI FORUM KOORDINASI PEMERINTAHAN DAERAH (FORKOPIMDA) DALAM SISTEM PEMERINTAHAN DAERAH DI INDONESIA - Sri Maulidiah (UIR Press, 2018)
Local government together with the Regional Perwakuilan Rakyat (DPRD) held local government and assisted by elements of regional tools related to the implementation of the affairs that become the authority of local government. In the implementation of regional government elements of local government together with the Regional People's Legislative Assembly to organize local government and assisted by elements of regional tools related to the implementation of the affairs that become the authority of local government. In certain matters, the local government is assisted by other elements such as vertical institutions in the region, in the form of the administration of public affairs and other residual matters. In this regard, in Law No. 23 of 2014 on Regional Government, a forum called the Coordination Forum for Regional Leaders or shortened with FORKOPIMDA should be established. FORKOPIMDA formerly called this element of deliberation of regional leadership or abbreviated with MUSPIDA. in carrying out its function FORKOPIMDA still find various problems, such as budgetary sources, management FORKOPIMDA, organizational structure, and so forth. The Regional Leadership Coordination Forum was established based on Law Number 23 of 2014 on Regional Government. Historically the Regional Leadership Coordination Forum was in the form of a Regional Leadership Council or abbreviated as MUSPIDA, the function of Forkopimda is to support the implementation of general government affairs by local governments Activities associated with FORKOPIMDA are funded through the State Budget and Expenditure Budget. It is suggested to the government to immediately issue a government regulation on FORKOPIMDA. It is recommended to Provincial and District / City region to take initiative in tackling the cost of organizing general government affairs. It is advisable to the government to immediately issue a government regulation on FORKOPIMDA and to Provincial and District / City Offices.